Wolbachia as a bacteriocyte-associated nutritional mutualist - Hosokawa, Takahiro (National Academy of Sciences, 2009)
Many insects are dependent on bacterial symbionts that provide essential nutrients (ex. aphid–Buchnera and tsetse–Wiglesworthia associations), wherein the symbionts are harbored in specific cells called bacteriocytes that constitute a symbiotic organ bacteriome. Facultative and parasitic bacterial symbionts like Wolbachia have been regarded as evolutionarily distinct from such obligate nutritional mutualists. However, we discovered that, in the bedbug Cimex lectularius, Wolbachia resides in a bacteriome and appears to be an obligate nutritional mutualist. Two bacterial symbionts, a Wolbachia strain and an unnamed γ-proteobacterium, were identified from different strains of the bedbug. The Wolbachia symbiont was detected from all of the insects examined whereas the γ-proteobacterium was found in a part of them. The Wolbachia symbiont was specifically localized in the bacteriomes and vertically transmitted via the somatic stem cell niche of germalia to oocytes, infecting the incipient symbiotic organ at an early stage of the embryogenesis. Elimination of the Wolbachia symbiont resulted in retarded growth and sterility of the host insect. These deficiencies were rescued by oral supplementation of B vitamins, confirming the essential nutritional role of the symbiont for the host. The estimated genome size of the Wolbachia symbiont was around 1.3 Mb, which was almost equivalent to the genome sizes of parasitic Wolbachia strains of other insects. These results indicate that bacteriocyte-associated nutritional mutualism can evolve from facultative and prevalent microbial associates like Wolbachia, highlighting a previously unknown aspect of the parasitism-mutualism evolutionary continuum.